The role of institutions in the history of Latin America - Ayala Mora, Enrique (2024)
Against this background, what I am going to do here is an ambitious sketch of Latin America, of the role of institutions in the evolution of the region. Latin America, of the role of institutions in the evolution of the region. As a professor of Latin American history, I am going to offer some reflections on how institutions in the continent have been participating in the construction of society and democracy; how the management of those institutions in the region has the construction of society and democracy; how the management of these institutions has been a fundamental element. institutions has been a fundamental element.